THE ROLE OF INFORMATION TECHNOLOGY IN THE EVOLUTION OF ORGANIZATIONAL COMMUNICATION PRACTICES - Syarifuddin; Indah Sulistiani; Suroso (ADISAM PUBLISHER, 2024)
Organizational communication is a very complicated and complex process of sending and receiving information within an organization. An organization that has an effective communication process will naturally advance and grow, and its members or individuals will actively contribute to the establishment and growth of an organization that is already functioning well in a number of areas, including organizational communication. The role of information technology is needed in the organizational world as a tool in an effort to win the competition that inevitably occurs in the organizational world. The role of information technology in organizations enables every process carried out to be easier and faster. This article's methodology is library research that reveals theories about the issue under study. The definition and concept of organizational communication, the evolution of communication and information technology, the incorporation of technology into organizational communication, and the influence of technology on organizational communication practices are all covered in this study